Perbandingan Skala ELPO Standar dan Modifikasi Dalam Deteksi Risiko Pressure Injury Pasien Bedah - Widiastuti, Heti; Winarto, Eko; Agusman, Fery (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Introduction: Patients undergoing surgery lasting more than two hours are at high risk of developing pressure injuries. To predict this risk, nurses can use the ELPO Scale, which assesses factors such as duration of surgery, body position, anesthesia, support, age, length of surgery, and comorbidities. This study aims to compare the results of the standard ELPO Scale with the modified ELPO Scale based on Myra Levine's Conservation Theory in detecting the risk of pressure injuries in patients undergoing surgery for more than two hours. Methods: This is a descriptive quantitative study with a retrospective case-control design using Chi-square analysis to assess the accuracy, sensitivity, and specificity of both scales. Results: The standard ELPO Scale did not show a significant relationship with the incidence of pressure ulcers. In contrast, the modified ELPO Scale had higher accuracy, sensitivity, and specificity in early detection. Conclusion: The modified ELPO Scale is more sensitive than the standard ELPO Scale in detecting the risk of pressure ulcers in surgical patients, with the factors of surgical position, age, mobilization, and skin moisture playing an important role in the occurrence of pressure ulcers.